Implementation of Teaching Games for Understanding to Stimulate Game Understanding of Elementary School Students (Universitas Pendidikan Indonesia, 2024)
Traditional physical education approaches, which often focus on decontextualized sports techniques, may affect the student engagement leading to learning difficulties. The Teaching Games for Understanding (TGfU) model, which emphasizes game understanding and skill development through actual plays, offers a pedagogical alternative. This study aimed to assess the effectiveness of using TGfU with modified traditional games, specifically the Kasti game, to improve the game understanding of primary school students. The pre-experimental design, specifically the One Group Pretest-Posttest Design, was used. This study involved 24 Grade 5 students from a public primary school in West Kalimantan, Indonesia. The TGfU model was implemented using a modified version of the Kasti game adapted to the school curriculum. The game comprehension was measured using the Game Performance Assessment Instrument (GPAI), focusing on decision-making, skill execution, and covering ability. Data were analyzed using descriptive statistics and t-tests to compare pretest and posttest results. Results of this study found a significant improvement in the student game comprehension after the intervention. The mean scores for skill execution, decision-making, and covering ability increased the overall game understanding from the pretest mean of 0.61 to the posttest mean of 0.67. The number of students categorized in the Effective Performance category increased, indicating improved cognitive and tactical understanding. The study concludes that TGfU, which incorporates modified traditional games, could effectively improve game understanding of primary school students. This approach could enhance student cognitive abilities and increase their enjoyment and engagement in sports. These findings suggest that TGfU is a viable model for teaching physical education.